Potential distributions of phlebotomine sandfly vectors of human visceral leishmaniasis caused by Leishmania infantum in Morocco. Issue 4 (26th February 2020) - Daoudi, M.; Boussaa, S.; Hafidi, M.; Boumezzough, A.
Abstract: Zoonotic visceral leishmaniasis is a common vector‐borne systemic disease caused by Leishmania infantum (Kinetoplastida: Trypanosomatidae) . In Morocco the situation is complex: many sandfly species have been collected in areas in which the disease is endemic, but only Phlebotomus ariasi, Phlebotomus perniciosus and Phlebotomus longicuspis (Diptera: Psychodidae) have been confirmed to have vectorial roles. The objective of the present study was to ascertain the potential distribution of L . infantum and its vectors in Morocco, using ecological niche modelling. Vector records were obtained from field collections of the Laboratory team and from previously published entomological observations. Epidemiological data for L. infantum modelling were obtained from Moroccan Ministry of Health reports. The jackknife test indicated that the bioclimatic variables with the greatest influence on model development for all species were annual precipitation and precipitation in the driest quarter of the year. MaxEnt model representations for sandfly species that act as vectors of L. infantum showed the widespread geographic distribution of these species in Morocco, specifically in northern and central Morocco, where foci of visceral leishmaniasis are found. The ecological niche modelling points out areas in which the probability of occurrence of these species is higher. This information should be considered as a starting point for further research to fully elucidate the ecology and epidemiology of these species, as well as of the pathogens they transmit. Abstract : MaxEnt models were used to estimate the potential distributions of human visceral leishmaniasis caused by Leishmania infantum and its sandfly vector species in Morocco. The most important variables for the model were annual precipitation and precipitation in the driest quarter of the year. MaxEnt model representations for sandfly vectors of L. infantum showed the widespread geographic distribution of these species, specifically in northern and central Morocco, where foci of visceral leishmaniasis occur.